(untitled) (American Journal of Technology and Applied Sciences, 2024)
Metabolically Associated Fatty Liver Disease (MAFLD) has emerged as a significant public health concern, driven by rising global obesity rates and metabolic syndromes. This paper reviews the existing evidence on the efficacy and safety of Ursodeoxycholic Acid (UDCA) for the treatment of MAFLD, discussing the biochemical and physiological mechanisms through which UDCA may exert its effects. Furthermore, we will explore future research avenues and clinical implications.